Flora leñosa en dos áreas de la zona Reservada Bosque de Zárate, San Bartolomé, Huarochirí, Lima - Perú - Jimenez-Carlos, Lizett Cristina (2024)
The objective of this study was to evaluate the woody flora of the Zárate Forest Reserved Zone (ZRBZ). The methodology consisted of intensive botanical collections in two areas of the ZRBZ. We identified 14 botanical species distributed in the families Asteraceae, Berberidaceae, Rosaceae, Solanaceae, Escalloniaceae, Myrtaceae, Araliaceae, Verbenaceae, Euphorbiaceae, Scrophulariaceae y Loranthaceae. Two species are identified as endemic. According to the International Union for Conservation of Nature (IUCN), one species is in the Near Threatened (NT) category. According to national legislation (Supreme Decree 043-2006-AG), one species is Critically Endangered (CR) and two species are Vulnerable (Vu). Likewise, it was found that the woody flora identified has various uses such as timber, medicinal and agroforestry, among the most important ones. Finally, it is concluded that it is necessary to update the list of flora species for each area of the ZRBZ, which can contribute to improving its management.